1986
DOI: 10.1042/cs0710319
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide: Physiological release associated with natriuresis during water immersion in man

Abstract: Thermoneutral water immersion produces a physiological increase of thoracic blood volume, raises central venous pressure and increases urinary sodium excretion by a hitherto ill-understood mechanism. We have investigated whether this enhanced sodium excretion could be mediated by the recently discovered natriuretic factor, atrial natriuretic peptide (ANP). During water immersion there was a highly significant (P less than 0.001) twofold increase of the mean plasma ANP concentration and a doubling of the mean u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(20 citation statements)
references
References 0 publications
1
17
0
2
Order By: Relevance
“…A close relationship between plasma concentrations of ANP and right and left atrial pressures [8][9][10][11][12], as well as atrial dimensions [12], has been observed in humans. Acute alterations in atrial wall stress, induced by volume loading [8,11,13], headout-water-immersion [14], o1" physical exercise [15] were shown to induce rapid and pronounced changes in circulating ANP levels in humans.In patients with congestive heart failure, abnormal sodium and water retention is a well-known clinical phenomenon, which is primarily due to an increased activity of the sympathetic and renin-angiotensin systems and of vasopressin [16]. Since ANP is integTated into the homeostatic regulation of fluid and electrolyte balance [for review see 2, 3], a "relative" deficiency of circulating ANP in patients with congestive heart failure may be assumed.…”
mentioning
confidence: 99%
“…A close relationship between plasma concentrations of ANP and right and left atrial pressures [8][9][10][11][12], as well as atrial dimensions [12], has been observed in humans. Acute alterations in atrial wall stress, induced by volume loading [8,11,13], headout-water-immersion [14], o1" physical exercise [15] were shown to induce rapid and pronounced changes in circulating ANP levels in humans.In patients with congestive heart failure, abnormal sodium and water retention is a well-known clinical phenomenon, which is primarily due to an increased activity of the sympathetic and renin-angiotensin systems and of vasopressin [16]. Since ANP is integTated into the homeostatic regulation of fluid and electrolyte balance [for review see 2, 3], a "relative" deficiency of circulating ANP in patients with congestive heart failure may be assumed.…”
mentioning
confidence: 99%
“…Results derived from ani mal experiments predict ANP increases that are most likely mediated by a combination of atrial stretch and/or pressure [10], while in vitro studies independently elaborated atrial tension and rate of contraction in ANP release [11]. The latter observation is sup ported by the finding of increased ANP val ues in humans during exercise to levels seen in pathological hypervolemic states [12], Other maneuvers known to influence atrial stretch and venous return thereby causing ANP release are postural changes, such as head-down tilt, recumbency [12] and headout water immersion [13].…”
Section: Identification Release and Biological Effects Of Atrial Natmentioning
confidence: 98%
“…1) [28][29][30] or water [31 ], an acute increase in sodium intake [28,32,33], a central shift of volume produced by the change from the upright to the supine position ( fig. 1) [30,33,34] or by immersion into water [35,36], a vaso constrictor hormone-induced acute increase in blood pressure (BP) and. hence, afterload ( fig.…”
Section: Regulation Of Plasma Anp In Normal Humansmentioning
confidence: 99%